Implementasi Layanan Bimbingan Klasikal Model Problem Based Learning Untuk Mencegah Kenakalan Remaja - Istiqhfarin, Annisa Andalutia; Christiana, Elisabeth; Nursilowati, Lilik (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
Juvenile delinquency is a social problem that requires effective and sustainable prevention strategies. This study aims to evaluate the implementation of classical guidance services with the Problem-Based Learning (PBL) model to prevent juvenile delinquency in the school environment. Problem-Based Learning (PBL), which focuses on collaborative problem solving, is considered an effective model in helping adolescents develop problem-solving and critical thinking skills, which can reduce their tendency to engage in deviant behavior. This study used the counseling guidance action research (PTBK) method with the problem-based learning (PBL) model. We collected data by observing behavior and conducting interviews with students. The results of the study indicate that the implementation of classical guidance with problem-based learning (PBL) can significantly prevent juvenile delinquency, improve social skills, and improve student behavior. These findings emphasize the importance of implementing innovative and problem-based classical guidance services in efforts to prevent juvenile delinquency and provide valuable insights for the development of more effective classical guidance services.